Assessment of student misconceptions on basic concepts of measurement and matter : suggested activities for conceptual change - Resullar, Charissa Mae D (Archīum Ateneo, 2004)
This study aimed to assess common misconceptions or alternative conceptions on some chemistry concepts, e.g. measurement and matter, prevalent among high school chemistry students of the Ateneo de Zamboanga University.